2001
DOI: 10.1159/000055773
|View full text |Cite
|
Sign up to set email alerts
|

Tympanoscope-Assisted Myringoplasty

Abstract: Thirty ears of 29 patients with different sized perforation of the tympanic membrane were operated on with the aid of rigid otoendoscopes. The technique has a significant novel feature: endoscopy of the tympanic cavity through a perforation with small tympanoscopes 1.7 mm in diameter with a 0%. The postoperative air-bone gap was less than 10 dB in 90% of the ears. It was concluded that tympanoscope-assisted myringoplasty is a reliable and simple procedure with the benefit of minimal trauma in healthy tissue an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
44
2
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 10 publications
11
44
2
7
Order By: Relevance
“…Scope has to be held in one hand and other hand is free to operate and this becomes cumbersome when there is excessive bleeding, which can be managed easily in microscope assisted ear surgery where one hand can be used to suction the blood and simultaneously the other hand can be used to operate. We confirm these observations which were reported in studies by Tarabichi [1] and Karhuketoet al [12]. This problem can be solved by developing a stand for endoscope which will fix it in desired position so that both the hands will be free to operate.…”
Section: Discussionsupporting
confidence: 90%
“…Scope has to be held in one hand and other hand is free to operate and this becomes cumbersome when there is excessive bleeding, which can be managed easily in microscope assisted ear surgery where one hand can be used to suction the blood and simultaneously the other hand can be used to operate. We confirm these observations which were reported in studies by Tarabichi [1] and Karhuketoet al [12]. This problem can be solved by developing a stand for endoscope which will fix it in desired position so that both the hands will be free to operate.…”
Section: Discussionsupporting
confidence: 90%
“…Excessive bleeding can be managed easily in microscope assisted ear surgery where one hand can be used to suck the blood and simultaneously the other hand can be used to operate; but only one hand is available to do both the jobs in endoscopic ear surgery. We confi rm these observations which were reported in studies by Tarabichi M [3] and Karhuketo TS, Ilomaki JH, Puhakka HJ [6]. This problem can be solved by developing a stand for the scope which will fi x it in the desired position so that both the hands will be free to operate.…”
Section: Discussionsupporting
confidence: 85%
“…9 Karchuketo TS studied the endoscopic assisted myringoplasty in 30 ears of 29 patients with different sized perforation & concluded that the post-operative air bone gap was less than 10 dB in 90% cases. 10 Hence endoscopic assisted myringoplasty is reliable and simple procedure with the benefit of minimal trauma to the healthy tissue.…”
Section: Complication Ratementioning
confidence: 99%